Expression of Constitutive Fusion of Ubiquitin to PCNA Restores the Level of Immunoglobulin A/T Mutations During Somatic Hypermutation in the Ramos Cell Line - Lerner, Leticia K.; Bonte, Dorine; Le Guillou, Morwenna; Mohammad, Mahwish Mian; Kasraian, Zeinab; Sarasin, Alain; Despras, Emmanuelle; Aoufouchi, Said (Frontiers in Immunology, 2022)
Somatic hypermutation (SHM) of immunoglobulin (Ig) genes is a B cell specific process required for the generation of specific and high affinity antibodies during the maturation of the immune response against foreign antigens. This process depends on the activity of both activation-induced cytidine deaminase (AID) and several DNA repair factors. AID-dependent SHM creates the full spectrum of mutations in Ig variable (V) regions equally distributed at G/C and A/T bases. In most mammalian cells, deamination of deoxycytidine into uracil during S phase induces targeted G/C mutagenesis using either direct replication of uracils or TLS mediated bypass, however only the machinery of activated B lymphocytes can generate A/T mutagenesis around AID-created uracils. The molecular mechanism behind the latter remains incompletely understood to date. However, the lack of a cellular model that reproduces both G/C and A/T mutation spectra constitutes the major hurdle to elucidating it. The few available B cell lines used thus far to study Ig SHM indeed undergo mainly G/C mutations, that make them inappropriate or of limited use. In this report, we show that in the Ramos cell line that undergoes constitutive G/C-biased SHM in culture, the low rate of A/T mutations is due to an imbalance in the ubiquitination/deubiquitination reaction of PCNA, with the deubiquitination reaction being predominant. The inhibition of the deubiquitinase complex USP1-UAF1 or the expression of constitutive fusion of ubiquitin to PCNA provides the missing clue required for DNA polymerase η recruitment and thereafter the introduction of A/T base pair (bp) mutations during the process of IgV gene diversification. This study reports the establishment of the first modified human B cell line that recapitulates the mechanism of SHM of Ig genes in vitro.